Study on Soil Pollution Control and Land Ecological Restoration Technology - Ma, Lin (International Journal of Natural Resources and Environmental Studies, 2024)
This paper discusses the present situation and development trend of soil pollution control and land ecological restoration technology. Soil pollution mainly comes from industrial emissions, excessive use of pesticides and fertilizers and improper treatment of municipal garbage, which poses a threat to agriculture, human health and ecological balance. Treatment technologies include engineering remediation (such as soil replacement and water washing), physical-chemical remediation (such as solidification-stabilization, leaching, etc.), and biological remediation (using microorganisms, plants and animals). Land ecological restoration emphasizes integrity and sustainability, and adopts various methods such as plant and microbial restoration. In addition, prevention and control strategies and policy suggestions are put forward, including strengthening waste treatment standards, rational use of pesticides and fertilizers, and promoting waste classification. It is also suggested to establish a sound legal system for soil pollution prevention and control and raise public awareness of environmental protection.